Pengaruh Pemberian Pupuk Hayati Petrobio Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Caisim (Brassica juncea L.) - rahmat samsudin (AGRONISMA, 2022)
Caisim mustard (Brassica juncea L.) is a type of leaf vegetable that contains a variety of complete nutrients that are widely used by the community. This study aims to obtain the optimum dose of biological fertilizer application that can increase the productivity of growth and yield of caisim mustard plants. The research was carried out on the agricultural land of the Sri Anom IV Temas farmer group, Batu District, Batu City for 2 months starting from December 2021 to January 2022. The design used was a Simple Randomized Design consisting of one factor, namely Petrobio (H) biofertilizer. Petrobio (H) biofertilizer application consists of 4 levels, namely H0 (without biofertilizer), H1 (50 kg/ha), H2 (100 kg/ha), H3 (150 kg/ha). From the design that has been described, each experimental unit was repeated 3 times and each treatment unit used 4 samples, so that 48 samples were obtained. The results of this study indicate that the application of Petrobio biofertilizer is able to provide real growth and yield of caisim mustard plants. The use of Petrobio H1, H2 and H3 biofertilizers gave an equally good response to the number of leaves. The H2 and H3 treatments gave the same good response to plant height and plant dry weight. While the H3 treatment gave an equally good response to plant fresh weight and plant economic weight. From the results of the regression analysis, the optimum dose of Petrobio biofertilizer was 174 kg/ha with an economic weight of 136.882 grams/plant.Keywords : Caisim mustard plant, Petrobio biofertilizer.